Confirming Proper Button Deployment of Suspensory Fixation During ACL Reconstruction. Issue 1 (19th January 2021) - O'Brien, Daniel F.; Fones, Lilah; Stoj, Victoria; Edgar, Cory; Coyner, Katherine; Arciero, Robert A.
Background: Suspensory fixation of anterior cruciate ligament (ACL) reconstruction (ACLR) grafts has emerged as a popular device for femoral graft fixation. However, improper deployment of the suspensory fixation can compromise proper graft tensioning, leading to failure and revision. Also, soft tissue interposition between the button and bone has been associated with graft migration and pain, occasionally requiring revision surgery. Many surgeons rely on manual testing and application of distal tension to the graft to confirm proper button deployment on the lateral cortex of the femur for ACL graft fixation. Purpose: To determine the reliability of the manual resistance maneuver when applying distal tension to deploy the suspensory device along the lateral cortex of the femur. Study Design: Case series; Level of evidence, 4. Methods: All patients undergoing ACLR with a suture button suspensory device for femoral fixation were eligible for enrollment in the study. The surgeries were performed by 3 board-certified, sports medicine fellowship–trained orthopaedic surgeons at a single outpatient surgical center between May 2018 and June 2019. All grafts were passed in a retrograde manner into the femoral tunnel, and a vigorous manual tensioning maneuver in a distal direction was placed on the graft to deploy and secure along the lateral cortex of the femur. Intraoperative mini c-arm fluoroscopy was obtained to demonstrate proper suture button positioning. If interposing tissue or an improperly flipped button was identified, rectifying steps were undertaken and recorded. Results: A total of 51 patients with a mean age of 33.3 years were included in the study. Of these patients, 74.5% had normal suture button positioning identified via intraoperative fluoroscopic imaging, while 15.7% had interposed soft tissue and 9.8% had an improperly flipped button. In all cases, the surgeon was able to rectify the malpositioning intraoperatively. Conclusion: Despite the manual sensation of proper suspensory button positioning, intraoperative fluoroscopy identified suture button deployment errors in ACLR 25% of the time. Correcting the malpositioning is not technically demanding. These findings advocate for routine intraoperative surveillance to confirm appropriate suture button seating during ACLR.